Utilizing Authentic Literature and Orai Application in Improving Students’ Literature Comprehension and Speaking Skills - Arida Susyetina (UICELL, 2019)
The rapid development of technology has brought a significant change in English classrooms. Nowadays, the use of technology plays a significant role in teaching and learning activities as students are more driven and enthusiastic when technology is utilized to facilitate learning. Orai application is proposed to improve students’ ability to comprehend authentic literature and speaking skills. The findings were classified into the students’ score improvement and the steps of teaching literature using Orai application. The improvement of students’ literature comprehension and speaking skills can be seen in the presentation delivered by the students and the increased score after the implementation of the teaching of speaking using Orai application in the first Cycle. The average score in the preliminary study was 61 while the average score at the end of implementation was 73. The overall result shows that Orai application was effective and beneficial to improve students’ comprehension of authentic literature and speaking skills. Keywords: authentic literature, ORAI application, comprehension, speaking skills